Factors related to professional self-concept of nursing students and nurses: A systematic review - I Gede Juanamasta; Yupin Aungsuroch; Sunida Preechawong; Joko Gunawan (Wolters Kluwer Medknow Publications, 2023)
Background: Some nurses leave their job because of working conditions, which will affect nurse turnover. Patients perceive that those nurses are distrustful, and feel unsatisfied, with patients' complaints about nursing service. This study explored factors about the professional self-concept of nursing students and nurses. Materials and Methods: A systematic review of cross-sectional studies followed PRISMA guidelines. PubMed, Ovid, Web of Science, and Cumulative Index to Nursing and Allied Health Literature (CINAHL) were used from 1982 to August 2020 with the terms "factors" AND "nurse" AND "professional" AND "self-concept." A total of 19 out of 4,349 articles were used for analysis. Joanna Brings Institute critical appraisal tools for the analytical cross-sectional studies were used in this study, and narrative synthesis was used to analyze data. Results: Professional self-concept of clinical nurses is influenced by including organizational or job factors, and individual and emotional factors. Job factors consist of organizational support, professional ethic, clinical ladder system, nursing experience, position, and time. Besides, sex, age, marital status, education, health status, healthy lifestyle, and experience were categorized as individual factors. Emotional factors were as follows: interpersonal relationships, spiritual growth, management stress, and self-description. Meanwhile, student nurses are influenced by including personal (degree of study and sex), emotions (emotional intelligence, and interest in the nursing profession), and external factors (nursing courses, peer-mentoring experience, and academic burnout). Conclusions: Thus, individual factors and emotions have a vital role in constructing clinical nurses' professional self-concept as student nurses. Improving individual and emotional/personal aspects will positively increase professional self-concept.